Entre a dança e o sacrifício: mito e rito nas coreografias de A sagração da primavera de Stravinsky e Roerich - Micieli, Diego Swerts (2019)
In an attempt to return to the essence of expressive human movement in the early 1900s, scenic dance went through a process of aesthetic and technical reconstruction. In this context, Polish dancer Vaslav Nijinsky elaborated a bold choreography for the ballet Le Sacre du Printemps – The Rite of Spring, by Igor Stravinsky and Nicholas Roerich. The show contains a dance that revisits the “primitive” situation of human existence and tells of a young peasant woman’s sacrifice to fertilize the earth and provide an abundant harvest. Throughout the years, numerous unique artists have choreographed this ballet, among them, French choreographer Maurice Béjart, in 1959, and German choreographer Pina Bausch, in 1975. Considering the mythical and ritualistic attributes of this composition, both in regard to its music and choreographed movements, the present work aims to approach and rethink the different choreographies of The Rite of Spring as expressions of a myth based mainly on the conceptions elaborated by Claude Lévi- Strauss. It also intends to explore the relations between rite, myth, and dance. In order to do so, the research relies on the audiovisual registrations of all three choreographies as source material. To facilitate analysis, it follows fragments of the libretto written by Stravinsky and Roerich. Next, it makes a comparative analysis of the fragments (or mythemes, according to Lévi-Strauss), in the three choreographies, noting suppressed, added or repeated themes in each of the performances. The research concludes with an analysis of the acquired content based on different theories of myth, rite, and sacrifice, and establishes connections between the contents of these theories within the framework history of dance